CORROSION EFFECT ON INTEGRITY OF EXISTING OFFSHORE FIXED PLATFORM - Kong , Jian Fang (Universiti Teknologi PETRONAS, 2020)
In this new decade, oil and gas industry remain necessary for the maintenance of industrial civilization in its current configuration making it a critical concern for many nations. However, with more platforms now operating beyond their design life, especially in Malaysian water where majority are jacket structures, structural integrity has risen as one of the most debated issues in the industry. In fact, corrosion represents one of the major causes of structural deterioration in offshore structures. With the above issues in mind, the effect of corrosion on the structural integrity of an existing platform is scrutinized based on the objectives set out for this study.